Study of Effective Utilization of WTP Sludge and Fly Ash in Brick Manufacturing: An Environmentally Friendly and Cost-Effective Approach to Brick Manufacturing Using WTP Sludge and Fly Ash (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Bricks are one of the most important construction material which are highly durable and used for the purpose of creating partition walls and have been used in the construction industry since thousands of years. The researches carried out in the past have witnessed making changes in the properties of bricks by making use of different foreign materials and to make the brick manufacturing process as sustainable and cost effective as possible. An attempt has been made in the following research to incorporate the use of WTP sludge and fly ash as an alternative material in the brick manufacturing process and observing the different properties of bricks and assessing the suitability of such bricks as per relevant codes of practice. Studies have revealed that the WTP sludge and fly ash have properties resembling to the clay used for manufacturing of traditional clay bricks. The disposal of WTP sludge and fly ash is done in an unscientific manner causing harmful effects on the environment. The utilization of WTP sludge and fly ash in manufacturing of bricks is an environment friendly solution and cost-effective. The combination of WTP sludge, fly ash and clay in manufacturing of bricks has shown promising results conforming to the relevant codes of practice.